Sistem Informasi Penjualan dan Persediaan Barang Dengan Metode Economic Order Quantity Pada PT. Dwi Surya Jakarta - Maria Maria; Dany Yudha Krisna; Gita Cahyani Lestari (Publikasi Indonesia, 2025)
This research aims to design and implement a sales and inventory information system that is integrated with the Economic Order Quantity (EOQ) method at PT. Dwi Surya Jakarta. The main problems faced by companies are difficulties in determining the optimal number of orders, frequent oversupply or shortage of stock, and manual recording of sales transactions. This study uses the System Development Life Cycle (SDLC) approach of the Waterfall model, which includes the stage of system analysis, design, implementation, and testing. The results show that the application of the EOQ method can help companies in determining the number of orders that are economical, reducing storage costs, and improving inventory management efficiency. The developed web-based information system is able to display stock reports in real-time and make it easier for management to make decisions.